Should Indonesia Learn from Malaysia and Singapore’s Cross-Border Insolvency Asset Settlements? - Wijayanta, Tata; Adistia, Sheva Trisanda; Leonardus, Rado F; Hermawan, B.E (Faculty of Law, Universitas Sebelas Maret, 2024)
The lack of boundaries between countries characterises the current globalisation. This convenience represents